Information relationships of structural components in the biotechnical system of correction of homeostasis - Поліщук, С. Т. (Proceedings of National Aviation University (archive), 2002)
Hemodialysis is considered as the process of extracorporal normalization of the biochemical composition of the human body fluid in the biotech system, the structure of the system from the standpoint of the theory of automated control, the information description, the interconnections of the structural components of the system and the algorithm of work.